Analysis of students' difficulties in the curricular component of chemistry from the contents addressed in ENEM (Research, Society and Development, 2021)
Education in Brazil faces some difficulties, and these are reflected in the results of internal and external evaluations. These results show the difficulties that students have in learning and understanding the contents of chemistry. The objective of this work is to carry out an analysis of the difficulties reported by students in the 3rd year of high school in a regular public school, located in Pecém (municipality of São Gonçalo do Amarante - CE), considering the Chemistry contents covered in the National Exam of High School - ENEM. This work is characterized as applied research, of a quantitative and exploratory nature. A questionnaire was applied, with the recurrent contents in ENEM, to understand in which subjects the students had more difficulties and based on this, to discuss this information in the light of theorists linked to the main current pedagogical trends. The results of this research showed that the contents that presented the worst performance by the students were: organic compounds and stoichiometric calculations, which require prior knowledge of calculations, as well as interpretation to identify oxygenated functions and understand their nomenclature.